2011
DOI: 10.3109/17482968.2010.517850
|View full text |Cite
|
Sign up to set email alerts
|

Progressive and widespread brain damage in ALS: MRI voxel-based morphometry and diffusion tensor imaging study

Abstract: We investigated 17 patients with sporadic amyotrophic lateral sclerosis (ALS) using voxel-based morphometry (VBM) and voxel-based analysis of diffusion tensor images (DTI) at baseline and after a six-month follow-up. Compared with 17 healthy controls, ALS patients at baseline showed only minimal white matter volume decreases in the inferior frontal gyrus but marked decreases in the gray matter of several regions, especially in the bilateral paracentral lobule of the premotor cortex. DTI revealed reduced fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 41 publications
11
60
0
1
Order By: Relevance
“…The spatial distribution of brain atrophy in ALS patients in this study was consistent with those observed in previous studies [31,35]. In the white matter, atrophy was shown only in the midbrain corresponding to the pyramidal tract.…”
Section: Pre-illnesssupporting
confidence: 91%
See 1 more Smart Citation
“…The spatial distribution of brain atrophy in ALS patients in this study was consistent with those observed in previous studies [31,35]. In the white matter, atrophy was shown only in the midbrain corresponding to the pyramidal tract.…”
Section: Pre-illnesssupporting
confidence: 91%
“…These FA and MD images were normalized to MNI space using the transformation matrix obtained when the EPI was normalized to the T2-weighted template image by a 12-parameter affine model, using the SPM5 module [27]. Finally, these normalized FA and MD maps were smoothed with an 8-mm isotropic Gaussian kernel [31].…”
Section: Voxel-based Diffusion Data Analysismentioning
confidence: 99%
“…Moreover, this is not the first study in which ALS effects were manifest as lateralized in the motor system. 4,10,15,20,37,43,44 Our findings are also in agreement with the descriptions of asymmetry in ALS pathology of the CSTs, 45 though a correspondence between the side of greater MR imaging differences and the side of greater muscle strength deficit of the limbs was not found, 10 probably because the muscle-strength score is a result of the upper and lower motor neuron involvement, whereas MR imaging detects only the UMN damage.…”
Section: Discussionsupporting
confidence: 80%
“…35 According to previous neuropathologic findings, 27,34,36 ALS degenerative changes in the cerebral cortex mainly involve motor areas, though recent whole-brain voxel-based morphometry analyses have largely reported GM abnormalities even in extramotor regions. 12,14,15,20,31,37 Thereby, the trends of MD and RD changes, which largely overlapped in our patients in both the genu and splenium of the CC, may represent an increase in the extracellular volume secondary to axonal loss associated with injury to the myelin sheaths, as previously reported in human and animal models of demyelination and axonal degeneration. 2,38,39 Thus, our results also suggest that in advanced stages of ALS, FA changes in the middle body of the CC reflect the degenerative process of axonal damage, inducing loss of motor function, whereas the increase in RD and MD in both the genu and splenium of the CC reflect more subtle axonal damage that could affect fine motor or extramotor skills.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation